Pelatihan Teknik Perawatan Koleksi Museum Kekhatuan Semaka - Risma Margaretha Sinaga; Sujarwo; Novia Fitri Istiawati (Nuwo Abdimas, 2023)
Museums are institutions, places of storage, care, security, and utilization of material evidence of human culture, nature and the environment to support efforts to protect and preserve the nation's cultural wealth. the existence of a museum that includes cultural heritage buildings requires extra care. If humans have to bathe, exercise, and take care of the body to a beauty salon. The maintenance of the museum's collection in practice is carried out by conservators who have expertise in the fields of chemistry, physics, biology and materials science. Therefore, efforts from all elements ranging from owners, managers, stakeholders and the public are needed in knowing and understanding the basic concept of caring for a museum collection as an asset that must be maintained and remain sustainable. This epic merger requires considerable effort, because in some cases there are still owners or managers who take care of the museum individually do not know too much about the technique of caring for museum collection objects, in this case the Semaka Museum of Unity. Therefore, training is needed for the owners, managers and the community in terms of assistance in implementing the maintenance technique for the collection of the Semaka Kekhatuan Museum in Tanggamus Regency, Lampung province.